The Land Acquisition of Inundated Land for The Toll Road Project of Semarang-Demak Sea Embankment - Guntur Bagus Pamungkas (The Indonesian Journal of Planning and Development, 2021)
The land acquisition process has been viewed as the most challenging phase in developing road infrastructures in Indonesia. Since the northern coast serves as a vital road corridor to support efficient population mobility and goods transport, the government set to improve the connectivity infrastructure by constructing a toll road project in Semarang – Demak Sea embankment (TTLSD). However, the development of toll road infrastructure for public purposes is often complex because it needs the acquisition of a massive quantity of land. In contrast, land supply is minimal, especially in degraded coastal zones. The study aims to investigate the land acquisition process in the inundated land, which impacts economic and social aspects. The research uses a mixed-methods approach, incorporating quantitative and qualitative research methods and spatial-based analysis techniques that utilize geographical information systems and remote sensing. This analysis shows that the majority of land parcels (92%) in the TTLSD construction project site were inundated lands. This phenomenon resulted in a slow land acquisition process because there were no technical laws and regulations to determine the status of flooded land. There was no mechanism for the transfer of rights to land in Indonesia. Moreover, the land acquisition was hampered by inappropriate compensation, which could not meet the community's expectations, and there were no clear land boundaries due to the flood.